2022
DOI: 10.3390/mca27060090
|View full text |Cite
|
Sign up to set email alerts
|

Increased Material Density within a New Biomechanism

Abstract: A new mechanism, applied in this study as a biomechanical device, known as a Bioactive Kinetic Screw (BKS) for bone implants is described. The BKS was designed as a bone implant, in which the bone particles, blood, cells, and protein molecules removed during bone drilling are used as a homogeneous autogenous transplant at the same implant site, aiming to optimize the healing process and simplify the surgical procedure. In this work, the amount of bone that will be compacted inside and around the new biomechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The technique described is characterized by the simplicity of the procedure, reduced contact of the collected material with the external environment, and faster surgical procedure, which requires the basic skills necessary for any dental surgeon. As described in previous works [10], the BKS implant, when drilling into bone, can collect and compact the drilling chips, in this case, particulate bone, in its internal volume. In the technique proposed here, the BKS was removed after its insertion into the retromolar region of the mandible, to collect bone from this region (Figure 3) and graft it in (within BKS) in a surgical alveolus previously prepared for this purpose also in the same mandible (Figure 4).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The technique described is characterized by the simplicity of the procedure, reduced contact of the collected material with the external environment, and faster surgical procedure, which requires the basic skills necessary for any dental surgeon. As described in previous works [10], the BKS implant, when drilling into bone, can collect and compact the drilling chips, in this case, particulate bone, in its internal volume. In the technique proposed here, the BKS was removed after its insertion into the retromolar region of the mandible, to collect bone from this region (Figure 3) and graft it in (within BKS) in a surgical alveolus previously prepared for this purpose also in the same mandible (Figure 4).…”
Section: Methodsmentioning
confidence: 96%
“…In this paper, we present an experimental study in a synthetic human mandible, where the new biomechanical device, BKS [9][10][11][12][13], is used to remove bone, such as a rotatory instrument, from the mandible (retro-molar region), and immediately, without the manipulation of this bone graft, be introduced into a dental alveolus, created specifically for this study, filling the bone-deprived region with an autogenous bone while the BKS dental implant is screwed in place. With this technique, there is no need for the external manipulation of the bone graft, as the stabilization of the particulate bone is performed by the BKS dental implant itself.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new bioactive kinetic screw bone implant model efficiently accomplishes both autogenous grafting and sinus augmentation while also securing the implant in a single procedure. When the vertical bone height in the planned implant site is less than 4 mm, an additional surgical step is undertaken to harvest bone and enhance its availability [62][63][64][65][66]. Experimental studies conducted on synthetic maxillary bone and sinus have successfully demonstrated the feasibility and simplicity of this innovative technique.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…The use of a bone collection device in which the same procedures are applied in dental implantation makes the act itself similar the surgeon's normal routine, and we can predict similar expected results in terms of the patient's acceptance [1,3]. The new mechanical device, bioactive kinetic screw (BKS), described here is a simple multifunctional machine able to simultaneously drill and screw, measure the volume density of the material where it is applied, and compact the material inside [16][17][18][19][20]; here, we also describe another application, wherein the material collected in the device's interior volume can be used for transplantation to other regions for bone filling, or be used as a stimulus of osteogenesis, osteoinduction, and osteoconduction in bone scaffolds. The idea of reusing bone from bone drilling during dental implant insertion creates the concept of the BKS model as a bone collector [8,[16][17][18][19], which allows simultaneous drilling and screwing, and insertion of the cut material (bone chips) into the internal volume of this new BKS implant model, to then be transplanted.…”
Section: Introductionmentioning
confidence: 99%
“…These sizes can be modified internally (through flute length and width, diameter, and position in relation to the longitudinal axis of the through hole), as can the length and overall diameter of the screw. The larger the internal volume measurements of the BKS, the greater the bone collection capacity will be in proportion to the size of the total volume of BKS applied [19]. The choice of the amount of bone to be harvested, and therefore the size of the BKS, depends on the patient's needs, the surgeon's choice of the donor site, and the purpose of the graft (bone defect filling, or vertical or horizontal bone augmentation).…”
Section: Introductionmentioning
confidence: 99%